COMBATING DOMESTIC VIOLENCE – POLISH SYSTEMIC SOLUTIONS - Jolanta Mackowicz; Bozena Majerek (European Scientific Journal, ESJ, 2013)
The process of recognising domestic violence in Poland begun in 1990s, drawing the attention of the researchers mostly to parent-child abuse. In most such cases, using violence against children was deemed a necessary part of upbringing, a method of discipline forcing children to follow specific behaviour patterns. Social acceptance for corporal punishment was rooted in established moral standards, stereotypes and recurring nature of the cycles of violence across generations. Domestic violence is present in various relations (parent-child, partner-partner, younger-older) and is usually of hidden nature (except extreme cases), therefore, in the first place, the researchers focused on the attempt to assess the scale and effects of the problem (both direct effects, as well as long-term effects), establishing a support system for the victims, as well as educational impact both on national, as well as local levels aimed at changing the social attitude towards domestic violence. The main goal of this article is to present the Polish system for combating family violence in the light of the scale of the problem and various types of social attitude towards it. The following issues are discussed in this article: -established moral standards and stereotypes concerning domestic violence, especially corporal punishment for children - scale of the problem of domestic violence - strategies of helping the victims, including the structure of support institutions - strategies of intervention and correction actions against perpetrators, including the Blue Card procedure as the main intervention procedure used in Poland - education activities for both professionals and the society as a whole